The Case for Gay Rights : From Bowers to Lawrence and Beyond - Richards, David A. J. (Book collections on Project MUSE., 2005)
As Americans wrestle with debates over traditional values, defense of marriage, and gay rights, reason often seems to take a back seat to emotion. In response, legal scholar Richards reflects upon the constitutional and democratic principles--relating to privacy, intimate life, free speech, tolerance, and conscience--that underpin these often heated debates. The distillation of Richards's thirty-year advocacy for the rights of gays and lesbians, his book provides a reflective treatise on basic human rights that touch all of our lives. He places in context two key Supreme Court cases: the 1986 Bowers v. Hardwick decision, and the 2003 Lawrence v. Texas decision which overturned it. Drawing upon his own experiences as a gay man, Richards interweaves personal observations with philosophical, political, judicial, and psychological insights to make a case that gays should be entitled to the same rights and protections that every American enjoys.--From publisher description.